Pembuatan Desain Brosur Pembelajaran Proses Penanaman Sampai Pengolahan Kopi Berbasis Augmented Reality Di Gombengsari - Yulianto, Rachman; Eko Musantono, Agus; Maulana, Revan (Jurnal Informatika dan Komputer, 2024)
Video is a combination of multimedia elements that can display visuals, audio and text at one time. This research aims to create an Augmented Reality-based coffee planting brochure design using markers to produce educational videos that present realistic visualizations and can help provide supporting information that is easy to absorb and understand. The method used in making this learning media is the Multimedia Development Life Cycle with six stages, namely conceptualizing, designing, collecting material, assembling, testing, distributing. The application of augmented reality-based videos aims to increase the impression of learning the process of planting and processing coffee by presenting realistic visuals. For this reason, making a learning brochure on the process of planting and processing coffee based on augmented reality produces markers that can be read in lighting of 10 lux and above, markers in wet conditions, markers in crushed conditions, markers in scratched conditions, a maximum height of 90 cm, and different from smartphones. Problems with markers that cannot be read include torn markers, lighting below 10 lux, and a height of more than 90 cm.